PROSPECTIVE CRITICAL THINKING AND COGNITIVE STUDENTS BASED LEARNING THROUGH INQUIRY - Abdul Hamid (PROSIDING SEMINAR KIMIA, 2015)
The Study on critical thinking and cognitive prospective students through inquiry-based learning had been conducted. The aim of this study is to determine the critical thinking and cognitive prospects of senior high school students through the free and guided inquiry learning. The data had been gathered by using a quasi-experimental. The first step of this study was using non equivalent control group that was designed for SMA Negeri 11 to see the prospect of guided inquiry and also student’s cognitive and critical thinking. Next step, to improve students cognitive and critical thinking datagathered from SMA Negeri 1 Banjarmasin students to see prospective guided inquiry and free inquiry. The comparison between designed pre test-post test of these 2 groups analyzed.The study shows that (1) guided inquiry learning having more prospect compared to expository learning with value of N-gain 0.71 and 0.62 (2) free inquiry has more prospect in improving critical thinking than guided inquiry with a value of N-gain 0, 48 and 0.47. (3) guided inquiry has more prospect in increasing students cognitive value compared to free inquiry to the value of N-gain of 0.82 and 0.62.